Konsep Ulul Albab Dalam Manajemen Kepemimpinan Pendidikan Islam - Nimas Wegig Kurniana (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2020)
Leadership is the spearhead of the management of Islamic education. In essence every human being is a leader for himself, responsible for what happens to himself. Islam has the Messenger of Allah SWT as an example of a true leader. As khalifah fil ardh, man has the nature that exists in him to lead, both himself or an organization. The figure of the leader in the management of Islamic education is a prime mover figure and determinant in which direction an educational organization goes. Ulul alab leader character is a leader who has a high intellectual, always remaind and pray to Allah SWT. The main point in determining the figure of a leader in the management of Islamic education is the leader who leads in accordance with the teachings of the Islamic religion and the objectives of Islamic education.